Potential challenges and opportunities of the European Union Deforestation Regulation for New Zealand’s forestry sector - Xiwen Wang; Grace Villamor (Australian and New Zealand Journal of European Studies)
In 2023, the European Union (EU) announced its first-ever regulation on deforestation-free products. The European Union Deforestation Regulations (EUDR) aims to mitigate deforestation and forest degradation by regulating products associated with cattle, oil palm, rubber, soya, and wood. It mandates rigorous traceability of the related products throughout the supply chain and comprehensive compliance checks at the EU border. The EU is one of New Zealand’s (NZ) most significant trading partners in the world. The two parties concluded a Free Trade Agreement to boost bilateral trade further. Although forestry products make up a small portion of trade between the EU and NZ, they are NZ’s third-largest export, significantly contributing to its economic revenue. This highlights the significance of examining the impact of the EUDR on NZ’s forestry sector in maintaining continuous and steady economic growth. This paper aims to analyse the potential challenges and opportunities of the EUDR for NZ’s forestry sector.